2015
DOI: 10.1590/2317-1545v37n3150595
|View full text |Cite
|
Sign up to set email alerts
|

Germination inhibits the growth of new roots and seedlings in Eugenia uniflora and Eugenia brasiliensis

Abstract: -Seeds of Eugenia species can produce new roots and whole plants even when much of its reserves is removed. However, new roots and seedlings rarely are formed spontaneously, and after cutting, each seed fragment usually produces only one new seedling, suggesting some control of the formation of several seedlings. It is possible, therefore, that germination leads to the production of inhibitory substances avoiding the development of new embryonic tissues. In the present work we have analyzed the potential of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
8
0
2
Order By: Relevance
“…Such high numbers are common among recalcitrant seeds, and they have been observed in many species of the genus Eugenia (Delgado and Barbedo, 2012). Also, values similar to the ones presented on this work were detected by other authors in E. brasiliensis and E. uniflora (Amador and Barbedo, 2015). On the other hand, Lamarca et al (2011) and Amador and Barbedo (2011) found lower values in E. pyriformis.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Such high numbers are common among recalcitrant seeds, and they have been observed in many species of the genus Eugenia (Delgado and Barbedo, 2012). Also, values similar to the ones presented on this work were detected by other authors in E. brasiliensis and E. uniflora (Amador and Barbedo, 2015). On the other hand, Lamarca et al (2011) and Amador and Barbedo (2011) found lower values in E. pyriformis.…”
Section: Resultssupporting
confidence: 91%
“…As affirmed by Barbedo et al (2013), variations in the water content of seeds of a particular species might indicate differences in the maturation stages at the moment when they were detached from the parent plant. This fact could even be responsible for the level of recalcitrance of the seeds.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is rare the formation of more than one root or seedling from a single seed at the same time. Apparently, there is a well-established control to prevent reserves of being depleted in simultaneous germination, and a second root formation only begins when the first root is lost (Amador and Barbedo, 2011;Delgado and Barbedo, 2011;Amador and Barbedo, 2015). This allows the same seed to experience adverse conditions without necessarily losing the ability to propagate the species.…”
Section: Strategies To Ensure the Perpetuation Of The Species With Rementioning
confidence: 99%
“…Há, por exemplo, evidente controle interno para que as reservas da semente não sejam utilizadas em germinações simultâneas e, dessa forma, quando uma germinação se inicia há inibição da formação de novas raízes na mesma semente, como demonstrado em Eugenia uniflora L. e E. brasiliensis Lam. (Delgado & Barbedo 2011, Amador & Barbedo 2015. A quantidade de tecido de reserva parece também definir o sucesso da formação de novas plântulas, muitas vezes obtendo-se somente novas raízes (Prataviera et al 2015).…”
Section: Introductionunclassified